Comprehensive Midwifery Care for Ny "E" with a Normal Pregnancy at the Caile Community Health Center, Ujungbulu District, Bulukumba Regency for the Period May-July Year 2025 - Asmirati (Hayyan Journal, 2025)
Pregnancy, childbirth, newborns, the postpartum period, neonates and family planning are normal conditions, but require supervision so that they do not turn into abnormal conditions so that the government and health workers must make various efforts to treat and reduce complications that can cause morbidity and mortality. to the mother and baby by providing continuous care or comprehensive care to improve the health status of the mother and child through monitoring, development from pregnancy to family planning (KB). The care methods in this LTA are interviews, patient observations at the Community Health Center and home visits. The subject in this care is Mrs "E" GIPIA0 with a normal third trimester pregnancy at the Caile Community Health Center. Based on the results of comprehensive midwifery care for Mrs "E" by carrying out midwifery care independently and collaboratively during the third trimester of pregnancy with normal physiological complaints, in labor with spontaneous delivery, the baby was born normally, postpartum visits 4 times and neonate visits 3 times were normal as well as the use of contraception using injections, by documenting SOAP in the Varney management approach for pregnant women, giving birth, newborns, postpartum, neonates and services. Family planning. Conclusion Comprehensive Midwifery Care carried out on Mrs "E" starting from the gestational age of 34 weeks 3 days, delivery, newborns, postpartum, neonates and family planning (KB) with injections, normally without any accompanying complications or complications, it is hoped that the results of this writing can be a source of information and increase knowledge and skills in accordance with comprehensive midwifery care service standards in health services, especially at the Caile Community Health Center, UjungBulu District, Bulukumba Regency.